Silicoflagellates and ebridians from the New Jersey Transect DSDP Leg 93 - Kevin McCartney; Sherwood W Wise (PANGAEA, 1987)
Well-preserved and diverse silicoflagellate and ebridian populations are found in the lower and middle Eocene sediments of DSDP Site 605 and the upper Miocene sediments of DSDP Site 604. The ebridians outnumber the silicoflagellates in the siliceous interval of Site 605, but are less numerous at Site 604. The abundances of the various taxa are tabulated.
Supplement to: McCartney, K; Wise, SW (1987): Silicoflagellates and ebridians from the New Jersey Transect, Deep Sea Drilling Project Leg 93, Sites 604 and 605. In: van Hinte, JE; Wise, SW Jr; et al. (eds.), Initial Reports of the Deep Sea Drilling Project, Washington (U.S. Govt. Printing Office), 93, 801-814, https://doi.org/10.2973/dsdp.proc.93.127.1987